Transition metal/Photoredox catalyzed cascade reactions involving annulation for accessing functionalized heterocycles - Yadav, Pooja; Singh, Saumya; Shahid, M; Gopinath, Purushothaman (Synlett)
Cascade reactions are highly effective, atom- and step-economical processes in organic synthesis, which are widely used for the streamlined construction of various molecular architectures. Although there are several types of cascade reactions reported in the literature, one involving annulation as the key step is more captivating as it gives quick access to various heterocyclic compounds in a short and effective manner. In this account, our groups efforts towards cascade addition/functionalization followed by annulation of simple substrates for accessing various bio-relevant heterocycles and drug derivatives will be presented. We have used photocatalysis for cascade addition-annulation type reactions, transition metal catalysis for cascade C-H acyl methylation-annulation and finally dual transition metal- photoredox catalysis for cascade C-H olefination-annulation of carboxylic acids. Using these strategies, a broad range of structurally complex heterocyclic scaffolds, including dihydroquinazolinones, chromanes, benzoxazines, julolidine, etc. were synthesized.